Implementation of a Scientific Approach Using Problem Based Learning (PBL) Models to Improve Learning Outcomes of Overhand Pass In Volleyball Game - Indri Utami; Sudirman Burhanuddin; Sahabuddin Sahabuddin (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study is a classroom action research that aims to discover whether a scientific approach using a problem-based learning model can improve the learning outcomes of upper passing in volleyball for grade XI MIPA 2 at Ma Ma’arif Nu Lasepang in the Bantaeng district. A classroom action research employed the PBL model in its material, namely the basic technique of upper passing in a volleyball. The study was conducted in 2 cycles, each cycle consisted of 3 meetings. The aspects assessed in this study were spiritual KI- 1, social KI- 2, cognitive KI- 3, and psychomotor KI- 4. The research sample was 20 students. Based on the results of the study, at the beginning of the study, initial observation was conducted to determine the condition of students' initial data. As a reference in the assessment, the Benchmark Reference Assessment (PAP) on a scale of 5. In the initial data, it is discovered that no student can achieve the minimum completeness criteria. Furthermore, in the first cycle, there is an increase in the number of students who experienced mastery learning, namely 5 students with a percentage of 25% and there is a significant increase in the second cycle, namely 18 students with 90%.